Targeting oxidative stress, iron overload and ferroptosis in bone-degenerative conditions - Ren Junxiao; Meng Chen; Li Rui; Xu Yongqing; Li Chuan (Türk Biyokimya Dergisi)
Bone-degenerative conditions, including osteoporosis, rheumatoid arthritis, and osteoarthritis, are major public health concerns worldwide, associated with oxidative stress and iron overload that disrupts bone homeostasis. Ferroptosis, an iron-mediated form of cell death, has emerged as a critical factor in bone degeneration, necessitating a comprehensive review of its role in these conditions.